Formal solutions of singularly-perturbed linear differential systems. (September 2019) - Barkatou, Moulay A.; Maddah, Suzy S.
Abstract: In this article, we discuss formal invariants of singularly-perturbed linear differential systems in neighborhood of turning points and give algorithms which allow their computation. The algorithms proposed are implemented in the computer algebra systemMaple .